2017
DOI: 10.1016/j.gene.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Old age and the associated impairment of bones' adaptation to loading are associated with transcriptomic changes in cellular metabolism, cell-matrix interactions and the cell cycle

Abstract: In old animals, bone's ability to adapt its mass and architecture to functional load-bearing requirements is diminished, resulting in bone loss characteristic of osteoporosis. Here we investigate transcriptomic changes associated with this impaired adaptive response. Young adult (19-week-old) and aged (19-month-old) female mice were subjected to unilateral axial tibial loading and their cortical shells harvested for microarray analysis between 1 h and 24 h following loading (36 mice per age group, 6 mice per l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 59 publications
5
43
0
Order By: Relevance
“…This emphasises the importance of being careful when extrapolating responses in young animals to those in old ones. This may be particularly true in the case of PTH as we have recently reported basal and loading-responsive transcriptomic differences between tibiae of young and aged mice [31]. These include Wnt signalling and bioenergetics processes, both of which are involved in the anabolic effects of PTH [32], [33].…”
Section: Discussionmentioning
confidence: 95%
“…This emphasises the importance of being careful when extrapolating responses in young animals to those in old ones. This may be particularly true in the case of PTH as we have recently reported basal and loading-responsive transcriptomic differences between tibiae of young and aged mice [31]. These include Wnt signalling and bioenergetics processes, both of which are involved in the anabolic effects of PTH [32], [33].…”
Section: Discussionmentioning
confidence: 95%
“…Adaptation to mechanical loading is important for maintaining bone health throughout life, and impairments to bone adaptation responses, such as with aging, can contribute to diseases like osteoporosis. Previous studies indicate that bone's mechanosensing osteocytes are lost with aging (Galea et al, ; Mullender, van der Meer, Huiskes, & Lips, ; Tiede‐Lewis et al, ), and that surviving osteocytes may have impaired mechanotransduction responses (Chalil et al, ; Donahue, Jacobs, & Donahue, ; Holguin, Brodt, & Silva, ). Accordingly, while mechanical loading of bone via exercise is an effective method to increase peak bone mass in younger individuals (Greene et al, ; Kontulainen, Sievanen, Kannus, Pasanen, & Vuori, ; Warden et al, ; Weatherholt & Warden, ), exercise‐based approaches produce modest effects (at best) on bone properties in elderly subjects (Gomez‐Cabello, Ara, Gonzalez‐Aguero, Casajus, & Vicente‐Rodriguez, ; Karlsson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several causative factors for this blunted mechanical adaption phenomenon with aging have been suggested. For example, one study showed that aged cortical bone demonstrated an altered transcriptional response following mechanical loading, with a suppression of functional signaling cascades and a blunted activation timeframe downstream of loading as compared to loaded bones from younger subjects (Galea et al, ). Even in a sedentary state, aged cortical bone demonstrated an upregulation of TGF‐beta signaling and inflammatory TNF‐alpha signaling pathways, and a downregulation of Wnt pathway components and genes related to cell cycle progression (Galea et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the response seen after anabolic mechanical loading. 36-38 It is possible that at the time point analyzed, bones had reached a homeostasis where they were no longer perceiving a decrease in mechanical loading and were beginning to remodel. Although there was increased expression of osteogenic genes, the new bone formation in immobilized bones is likely to be of lower quality than in the controls.…”
Section: Discussionmentioning
confidence: 99%